2007
DOI: 10.1103/physrevc.75.024610
|View full text |Cite
|
Sign up to set email alerts
|

Extended optical model analyses of elastic scattering and fusion cross sections for theLi6+Pb208system at near-Coulom

Abstract: Based on the extended optical model approach in which the polarization potential is decomposed into direct reaction (DR) and fusion parts, simultaneous χ 2 analyses are performed for elastic scattering and fusion cross section data for the 6 Li+ 208 Pb system at near-Coulomb-barrier energies. A folding potential is used as the bare potential. It is found that the real part of the resultant DR part of the polarization potential is repulsive, which is consistent with the results from the Continuum Discretized Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 43 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…A short range potential V F + i W F is responsible for fusion, and a superficial potential V DR + i W DR for direct reactions. Gómez-Camacho et al [120,[131][132][133][134][135][136][137][138] and So et al [139][140][141][142][143][144][145] have used this approach to investigate several weakly bound systems ( 6,7 Li + 28 Si, 8 B + 58 Ni, 9 Be + 27 Al, 28 Si, 64 Zn, 144 Sm, 208,209 Pb). They found, for all systems studied, that the fusion imaginary potential W F presents the usual TA, whereas the direct reaction imaginary potential W DR shows a BTA behavior.…”
Section: Threshold Anomaliesmentioning
confidence: 99%
“…A short range potential V F + i W F is responsible for fusion, and a superficial potential V DR + i W DR for direct reactions. Gómez-Camacho et al [120,[131][132][133][134][135][136][137][138] and So et al [139][140][141][142][143][144][145] have used this approach to investigate several weakly bound systems ( 6,7 Li + 28 Si, 8 B + 58 Ni, 9 Be + 27 Al, 28 Si, 64 Zn, 144 Sm, 208,209 Pb). They found, for all systems studied, that the fusion imaginary potential W F presents the usual TA, whereas the direct reaction imaginary potential W DR shows a BTA behavior.…”
Section: Threshold Anomaliesmentioning
confidence: 99%
“…However, the 9 Be nucleus has an interesting structure known as the Borromean structure, in which the 9 Be consists of two alpha particles and one weakly bound neutron. 10 B is a weakly bound stable nucleus that may breakup into different partitions, the most energetically favorable being 10 B → 6 Li + 4 He (Q = -4.461 MeV) [2]. The 11 B nucleus is a strongly bound nucleus with the binding energy of 8.67 MeV in respect to the 7 Li + α channel decay, and has a nonzero ground state deformation indicating a nonspherical symmetric charge distribution [48].…”
Section: B Parametrization Of the Optical Potentialmentioning
confidence: 99%
“…Accordingly, the diffuseness parameter of real part is 0.624 fm for the 9 Be target, and the diffuseness parameter of imaginary part surface absorption is 0.582 fm for the 15 N target. While the radius parameters of real part are 0.810 and 1.060 fm for 10,11 B targets, respectively.…”
Section: B Parametrization Of the Optical Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective real potential strength may even show a declining trend with with further decrease in energy if the breakup coupling dominates over the conventional couplings at near barrier energies. Recently, So, et al [17] have shown, based on the extended optical model approach, that the real and imaginary polarization potential components for scattering of 6 Li from 208 Pb, when decomposed into direct and fusion contributions, satisfy the dispersion relation separately. The fusion part in this case showing a conventional threshold behaviour while the direct part exhibits a smooth and relatively weak energy dependence.…”
Section: Introductionmentioning
confidence: 99%